Activated receptors for peroxisomic proliferators. Its role in the atherosclerosis, obesity and high blood pressure. - Mikhail Benet Rodríguez; Yosvel Curbelo Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2004)
The receptors activated by peroxisome proliferators are a family of factors of transcription that belong to the superfamily of the steroid receptors and include tree subtypes which are PPARá, PPAR©¬ and PPAR ã. These receptors join to direct hexameric repetitions in the form of heterodimers with the retinoid receptor. PPAR receptors regulate the expressions of a great variety of genes that codify the proteins that are implied in the lipid metabolism, the energetic homeostasis, the cellular differentiation and the formation of tumours. This review describes the features, regulation and target genes of the PPAR receptor and the physiopathological and pharmacological implications of the regulation of the lipid and glucose metabolism, the energetic homeostasis ,hypertension and endothelial dysfunction.